Reduction of hepatorenal and pancreatic damage by Ferula elaeochytris extract in STZ induced diabetic rats. (2nd January 2021) - Uyar, Ahmet; Yaman, Turan; Keles, Omer Faruk; Alkan, Elif Ebru; Demir, Abdulbaki; Celik, Ismail; Yener, Zabit
ABSTRACT: The therapeutic potential and antioxidant capacity of Ferula elaeochytris extract (FE) in the liver, kidney and pancreas of rats with diabetes induced by streptozotocin (STZ) was assessed using biochemistry, histopathology and immunohistochemistry. Forty adult Wistar albino male rats were divided randomly into five groups of eight rats each. The normal control (NC) group was untreated. The diabetes control (DC) group was treated with STZ to induce diabetes. The diabetes + acarbose group (DAC) was treated with STZ, then with acarbose daily for 28 days. The diabetes + FE (DFE) group was treated with STZ, then FE daily for 28 days. DC rats had inflammatory cell infiltration, hydropic degeneration and necrosis, whereas the DFE rats exhibited nearly normal histology. Insulin immunostaining in the pancreatic beta cells was decreased in the DC group compared to the NC group, whereas the DFE group was similar to the NC group. Many serum biomarkers of damage to liver, kidneys or pancreas were elevated in the DC group compared to the NC group; these biomarkers were decreased in the DFE group. The DC group exhibited increased malondialdehyde levels and decreased levels of the antioxidant defense system constituents compared to the NC group. The level of biomarkers the DFE group was close to the NC group. FE exhibited a protective effect against tissue damage owing to its antioxidant activities and to its ability to effect regeneration of β-cells in STZ induced diabetic rats.